Problem: Given the following data:2C6H6 (l) + 15O2 (g) → 12CO2 (g) + 6H2O (l)     ΔG° = -6399 kJC (s) + O2 (g) → CO2 (g)                                     ΔG° = -394 kJH2 (g) + 1/2O2 (g) → H2O (l)                               ΔG° = -237 kJcalculate ΔG° for the reaction6C (s) + 3H2 (g) → C6H6 (l)

FREE Expert Solution

Given:

2C6H6 (l) + 15O2 (g) → 12CO2 (g) + 6H2O (l)     ΔG° = -6399 kJ
C (s) + O2 (g) → CO2 (g)                                     ΔG° = -394 kJ
H2 (g) + 1/2O2 (g) → H2O (l)                               ΔG° = -237 kJ

Overall Reaction: 6C (s) + 3H2 (g) → C6H6 (l)

Rearrange the reaction and adjust the ΔG° value accordintly:

• 2C6H6 (l) + 15O2 (g) → 12CO2 (g) + 6H2O (l)     ΔG° = -6399 kJ

Reverse the reaction, divide by 2, and change the sign of ΔG°:

6CO2 (g) + 3H2O (l) → C6H6 (l) + 15/2O2 (g)   ΔG° = 6399 kJ/2 = 3199.5 kJ

• C (s) + O2 (g) → CO2 (g)                                     ΔG° = -394 kJ

Multiply the reaction and ΔG° by 6:

6C (s) + 6O2 (g) → 6CO2 (g)                                     ΔG° = 6(-394 kJ) = -2364 kJ

• H2 (g) + 1/2O2 (g) → H2O (l)                               ΔG° = -237 kJ

Multiply the reaction and ΔG° by 3:

3H2 (g) + O2 (g) → 3 H2O (l)                               ΔG° = 3(-237 kJ) = -711 kJ

89% (425 ratings)
Problem Details

Given the following data:

2C6H6 (l) + 15O2 (g) → 12CO2 (g) + 6H2O (l)     ΔG° = -6399 kJ
C (s) + O2 (g) → CO2 (g)                                     ΔG° = -394 kJ
H2 (g) + 1/2O2 (g) → H2O (l)                               ΔG° = -237 kJ

calculate ΔG° for the reaction

6C (s) + 3H2 (g) → C6H6 (l)